Combination of surface- and interference-enhanced Raman scattering by CuS nanocrystals on nanopatterned Au structures - Milekhin, Alexander G.; Yeryukov, Nikolay A.; Sveshnikova, Larisa L.; Duda, Tatyana A.; Rodyakina, Ekaterina E.; Gridchin, Victor A.; Sheremet, Evgeniya S.; Zahn, Dietrich R. T. (Beilstein Journal of Nanotechnology, 2015)
We present the results of a Raman study of optical phonons in CuS nanocrystals (NCs) with a low areal density fabricated through the Langmuir–Blodgett technology on nanopatterned Au nanocluster arrays using a combination of surface- and interference-enhanced Raman scattering (SERS and IERS, respectively). Micro-Raman spectra of one monolayer of CuS NCs deposited on a bare Si substrate reveal only features corresponding to crystalline Si. However, a new relatively strong peak occurs in the Raman spectrum of CuS NCs on Au nanocluster arrays at 474 cm−1. This feature is related to the optical phonon mode in CuS NCs and manifests the SERS effect. For CuS NCs deposited on a SiO2 layer this phonon mode is also observed due to the IERS effect. Its intensity changes periodically with increasing SiO2 layer thickness for different laser excitation lines and is enhanced by a factor of about 30. CuS NCs formed on Au nanocluster arrays fabricated on IERS substrates combine the advantages of SERS and IERS and demonstrate stronger SERS enhancement allowing for the observation of Raman signals from CuS NCs with an ultra-low areal density.
Keywords: copper sulfide (CuS) nanocrystals; interference-enhanced Raman spectroscopy; phonons; surface-enhanced Raman spectroscopy

(untitled) - Honma, I.; Sano, T.; Komiyama, H. (J. Phys. Chem., 1993)

(untitled) - Milekhin, A. G.; Yeryukov, N. A.; Sveshnikova, L. L.; Duda, T. A.; Kosolobov, S. S.; Latyshev, A. V.; Surovtsev, N. V.; Adichtchev, S. V.; Himcinschi, C.; Zenkevich, E. I.; Jian, W.-B.; Zahn, D. R. T. (J. Phys. Chem. C, 2012)

(untitled) - Hugall, J. T.; Baumberg, J. J.; Mahajan, S. (Appl. Phys. Lett., 2009)

(untitled) - Chursanova, M. V.; Dzhagan, V. M.; Yukhymchuk, V. O.; Lytvyn, O. S.; Valakh, M. Ya.; Khodasevich, I. A.; Lehmann, D.; Zahn, D. R. T.; Waurisch, C.; Hickey, S. G. (Nanoscale Res. Lett., 2009)

(untitled) - Lee, Y.-b.; Lee, S. H.; Lee, S.; Lee, H.; Kim, J.; Joo, J. (Appl. Phys. Lett., 2013)

(untitled) - Todescato, F.; Minotto, A.; Signorini, R.; Jasieniak, J. J.; Bozio, R. (ACS Nano, 2013)

(untitled) - Wang, X.; Kong, X.; Yu, Y.; Zhang, H. (J. Phys. Chem. C, 2007)

(untitled) - Shan, G.; Xu, L.; Wang, G.; Liu, Y. (J. Phys. Chem. C, 2007)

(untitled) - Liu, C. Y.; Dvoynenko, M. M.; Lai, M. Y.; Chan, T. H.; Lee, Y. R.; Wang, J.-K.; Wang, Y. L. (Appl. Phys. Lett., 2010)

(untitled) - Milekhin, A. G.; Yeryukov, N. A.; Sveshnikova, L. L.; Duda, T. A.; Zenkevich, E. I.; Kosolobov, S. S.; Latyshev, A. V.; Himcinschi, C.; Surovtsev, N. V.; Adichtchev, S. V.; Feng, Z. C.; Wu, C. C.; et al. (J. Exp. Theor. Phys., 2011)

(untitled) - Rumyantseva, A.; Kostcheev, S.; Adam, P.-M.; Gaponenko, S. V.; Vaschenko, S. V.; Kulakovich, O. S.; Ramanenka, A. A.; Guzatov, D. V.; Korbutyak, D.; Dzhagan, V.; Stroyuk, A. L.; Shvalagin, V. V. (ACS Nano, 2013)

(untitled) - Wang, Y.; Li, M.; Jia, H.; Song, W.; Han, X.; Zhang, J.; Yang, B.; Xu, W.; Zhao, B. (Spectrochim. Acta, Part A, 2006)

(untitled) - Yeryukov, N. A.; Milekhin, A. G.; Sveshnikova, L. L.; Duda, T. A.; Rodyakina, E. E.; Sheremet, E. S.; Ludemann, M.; Latyshev, A. V.; Zahn, D. R. T. (Thin Solid Films, 2013)

(untitled) - Li, J.-H.; Chen, S.-W.; Chou, Y.; Wu, M.-C.; Hsueh, C.-H.; Su, W.-F. (J. Phys. Chem. C, 2011)

(untitled) - Kahl, M.; Voges, E.; Kostrewa, S.; Viets, C.; Hill, W. (Sens. Actuators, B, 1998)

(untitled) - Guillot, N.; Shen, H.; Frémaux, B.; Péron, O.; Rinnert, E.; Toury, T.; Lamy de la Chapelle, M. (Appl. Phys. Lett., 2010)

(untitled) - Alvarez-Puebla, R.; Cui, B.; Bravo-Vasquez, J.-P.; Veres, T.; Fenniri, H. (J. Phys. Chem. C, 2007)

(untitled) - Nemanich, R. J.; Tsai, C. C.; Connell, G. A. N. (Phys. Rev. Lett., 1980)

(untitled) - Ishii, M.; Shibata, K.; Nozaki, H. (J. Solid State Chem., 1993)

(untitled) - Yoon, D.; Moon, H.; Son, Y.-W.; Choi, J. S.; Park, B. H.; Cha, Y. H.; Kim, Y. D.; Cheong, H. (Phys. Rev. B, 2009)

(untitled) - Kolobov, A. V.; Maeda, Y.; Tanaka, K. (J. Appl. Phys., 2000)

(untitled) - Marsillac, S.; Little, S. A.; Collins, R. W. (Thin Solid Films, 2011)

(untitled) - Aspnes, D. E.; Theeten, J. B. (J. Electrochem. Soc., 1980)

Microbeam Analysis - Nemanich, R. J. (Interference-enhanced Raman scattering from thin films and interfaces, 1989)

(untitled) - Seok, T. J.; Jamshidi, A.; Kim, M.; Dhuey, S.; Lakhani, A.; Choo, H.; Schuck, P. J.; Cabrini, S.; Schwartzberg, A. M.; Bokor, J.; Yablonovitch, E.; Wu, M. C. (Nano Lett., 2011)

(untitled) - Min, Q.; Pang, Y.; Collins, D. J.; Kuklev, N. A.; Gottselig, K.; Steuerman, D. W.; Gordon, R. (Opt. Express, 2011)

(untitled) - Gao, L.; Ren, W.; Liu, B.; Saito, R.; Wu, Z.-S.; Li, S.; Jiang, C.; Li, F.; Cheng, H.-M. (ACS Nano, 2009)

(untitled) - Wang, D.; Zhu, W.; Best, M. D.; Camden, J. P.; Crozier, K. B. (Nano Lett., 2013)

(untitled) - Milekhin, A.; Sveshnikova, L.; Duda, T.; Surovtsev, N.; Adichtchev, S.; Ding, L.; Zahn, D. R. T. (J. Vac. Sci. Technol., B, 2010)